Pengaruh Model Connected Mathematics Project Terhadap Kemampuan Pemahaman Konsep Matematika Ditinjau Dari Adversity Quotient - Farra Aulia Rahmayanti; Nur Baiti Nasution (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
This study aimed to determine whether the Connected Mathematics Project (CMP) instructional model enhances students' conceptual understanding compared to conventional teaching methods. Additionally, the research assessed differences in students' conceptual understanding based on their Adversity Quotient (AQ) categories: climbers, campers, and quitters. Furthermore, the study investigated whether there is an interaction between the CMP instructional model and Adversity Quotient in influencing students' conceptual understanding. The method employed was a quasi-experimental design with a posttest-only control group. The sample consisted of XI MIPA 2 as the experimental group and XI MIPA 4 as the control group. Data were collected using both test and non-test methods, and data analysis utilized a two-way analysis of variance (ANOVA). The findings revealed that the CMP instructional model significantly enhances students' conceptual understanding compared to the conventional model. Moreover, students categorized as climbers in AQ demonstrated better conceptual understanding compared to campers, while campers showed similar performance to quitters. Students with adversity quotient climbers exhibited better conceptual understanding than those with adversity quotient quitters. There was an interaction between the instructional model and adversity quotient in influencing conceptual understanding. Keywords: Adversity quotient, CMP, Conceptual understanding